2014
DOI: 10.1088/0004-637x/783/2/142
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Euv Coronal Holes and Open Magnetic Flux

Abstract: Coronal holes are regions on the Sun's surface that map the foot-prints of open magnetic field lines. We have developed an automated routine to detect and track boundaries of long-lived coronal holes using full-disk EUV images obtained by SoHO:EIT, SDO:AIA, and STEREO:EUVI. We measure coronal hole areas and magnetic flux in these holes, and compare the measurements with calculations by the PFSS model. It is shown that, from 1996 through 2010, the total area of coronal holes measured with EIT images varies betw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 40 publications
6
71
1
Order By: Relevance
“…The algorithm searches for a dominantlocal minimum in the intensity distribution for the EUV image. On average it lies between 55 ± 15 digital numbers (DN), consistent with the findings of Lowder et al (2014). If the algorithm is not able to detect a well defined minimum in the distribution, which is the case for images where 5% of the whole solar disc is covered by coronal hole pixels, the threshold is set to 55 DNs.…”
Section: Methodssupporting
confidence: 66%
See 2 more Smart Citations
“…The algorithm searches for a dominantlocal minimum in the intensity distribution for the EUV image. On average it lies between 55 ± 15 digital numbers (DN), consistent with the findings of Lowder et al (2014). If the algorithm is not able to detect a well defined minimum in the distribution, which is the case for images where 5% of the whole solar disc is covered by coronal hole pixels, the threshold is set to 55 DNs.…”
Section: Methodssupporting
confidence: 66%
“…The distribution of the solar wind is also decisive for deriving the propagation behavior of CMEs . The relationship between the size and location of CHs in the corona and the solar wind parameters and geomagnetic effects measured at 1 AU has been investigated by several groups (Nolte et al, 1976;Robbins, Henney, and Harvey, 2006;Vršnak, Temmer, and Veronig, 2007a,b;Luo et al, 2008;Abramenko, Yurchyshyn, and Watanabe, 2009;Obridko et al, 2009;de Toma, 2011;Verbanac et al, 2011;Lowder et al, 2014). In the early phases of coronal holes identification, CHs were visually tracked by experienced observers (Harvey and Recely, 2002;McIntosh, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found the distribution of magnetic null points in PFSS model fields (Cook, Mackay, and Nandy, 2009;Platten et al, 2014). The PFSS is, however, a theoretical model field known to depart from the field of the real solar corona (Lowder et al, 2014). One measure of the fidelity of the model could be obtained by comparing the number of null points predicted by the model to the number observed in coronal observations.…”
Section: Introductionmentioning
confidence: 99%
“…Krista and Gallagher (2009) use magnetic flux skewness to distinguish CHs from filaments, a threshold consistency test for robustness of their intensity thresholds, and solar wind data from ACE and STEREO to compare to CH locations. Lowder et al (2014) extend the method of Krista and Gallagher (2009) to use data from multiple instruments, study CH persistence, and compare CH magnetic flux to potential field source surface models. Caplan, Downs, and Linker (2016) propose point-spread function decovolution and limb brightening correction to normalize for instrumental variation and use a two-threshold region growing approach for segmentation of CHs and study CH persistence in SDO/AIA and STEREO/EUVI images.…”
Section: Introductionmentioning
confidence: 99%